A Taste for Habits: On Preference Self-Construction - Arielli, Emanuele (Aisthesis, 2024)
This paper explores the tensions and potential contradictions in the “self-construction” of habits and preferences, arguing that preferences and tastes not only arise from habit formation but also contribute to the development of new habits. Changing tastes necessitates self-reflection on our current preferences and habits, which then become subjects of evaluation, transformation, and alteration from a higher-order perspective. It will be argued that modifying the structure of one’s habits and preferences requires various forms of (self)-distancing: these include the impossibility of immediate transformation, recognizing the gradual nature of change, and acknowledging the limits of direct intentionality and control in the transformative process. These points ultimately reveal the inherent indeterminacy and openness of any self-cultivation endeavor involving preference-based habits, highlighting its balance between controllability and the potential for its loss.